INVENTORY OF HIGH LEVEL DIVERSITY PLANTS (SPERMATOPHYTA) AT HARAPAN BANGSA STADIUM LHONG RAYA CITY BANDA ACEH - Febriyanti, Dewi; Finzia, Pocut Zairiana; Hasanah, Mauizah (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
An inventory of the diversity of higher plants (Spermatophyta) at Harapan Bangsa Stadium, Lhong Raya, Banda Aceh, aims to determine the number of species found in the Harapan Bangsa Lhong Raya stadium as an effort to meet the needs of green open spaces in public facilities. The technique used is exploratory and roaming with purposive sampling. The results showed that the number of Spermatophyta plant species totaled 198 species, with the highest distribution from the casuarinaceae family 58 species, followed by anacardiaceae 25 species, lamiaceae 15 species, arecaceae 15 species, sapotaceae 15 species, arecaceae 13 species and rubiaceae 12 species, while the rest represented the Fabaceae, Myrtaceae, Nygtaginaceae, Oxalidaceae, Poaceae, Meliaceae, Arecaceae, and Caricaceae families. So it can be concluded that the Spermatophyta plants in the Lhong Raya stadium area have fulfilled the Green Open Space (RTH) requirements as a public facility. More research on the efficiency of green open space on oxygen supply in public environments is hoped for.Keywords: Inventory, Spermatophyta, Green Open Space (RTH)